Flutuação populacional da saúva do nordeste em ecossistemas distintos - Pereira, Rita de Cassia Alves (1994)
The investigation was carried out at Curu Valley Experimental Farm in Pentecoste County, State of Ceará, Brazil, from 1980 to 1981. Water pan traps and pitfall traps were adequate to assess the insect population dynamics in both the artificial and the natural ecosystems. Insect diversity was higher in the natural ecosystem made up of a bushy vegetation known as "caatinga". On the other hand the Northeast leaf-cutting ant, Atta opaciceps Borgmeier, 1939 (Hymenoptera : Fonnicidae) population in the artificial ecosystem, composed of a monoculture of buffel grass, Cenchrus ciharis, was ten times higher than that observed in the natural ecosystem. The research revealed that the simplification of the natural ecosystem (="caatinga") has modified the energy flow and favored eruption of primary consumers, specially those of the Insecta class.